THE INFLUENCE OF ORGANIZATIONS ON THE EFFECTIVENESS OF EDUCATIONAL PROGRAMS - Fauziyah, Nina; Azizah Putri, Nabila Aiz; Amaral Pinto, Siti Rosalinda (Institut Riset dan Pengembangan Indonesia, 2025)
Organizational adequacy may be a essential degree of success in satisfying parts and capacities to attain foreordained objectives. An organization is considered viable when it proficiently realizes the foreordained destinations. The term